Materiais nanoporosos para aplicação ambiental com ênfase na adsorção de contaminantes – estudos experimental e teórico - Aguiar, José Euranio de (2016)
Improper disposal of effluents containing contaminants can cause serious environmental problems. The dye can be highly toxic to aquatic systems; still in its composition may carries a high nutrient content can thus promote the process of eutrophication contributing to cyanobacterial bloom that can release toxins harmful to health of living beings. This study evaluated nanoporous materials as adsorbents, one Lamellar Double Hydroxide (LDH) two heterostructure Porous Lamellar (HPL), one pilarred clay the natural clay and five commercial activated carbon for adsorption and removal of dyes and neurotoxins. The materials were characterized by XRD, N2 adsorption-desorption, FTIR, XPS, SEM, elemental analysis, TPD to obtain information on their chemical, structural and textural characteristics. Experiments using a batch system of stirred tanks were performed to determine the effect of pH, contact time and the initial concentration in the adsorption of contaminants. The materials HPL type was evaluated for their ability adsorption of binary mixtures of dyes. Three of the activated carbons were evaluated in the adsorption of a neurotoxin (STX). For the tests in stirred tanks was used a rotary agitation system with acrylic tubes containing a predefined volume of dye and toxin solution in contact with a predetermined mass of adsorbent. The concentrations of the molecules were determined by spectrofotometric and HPLC methods for the dyes and toxins respectively with the aid of a mass balance of the initial phase and the fluid phase. In order to describe the behavior of adsorption isotherms, equilibrium data were correlated with the Langmuir (L), Langmuir-Freundlich (LF), Redlich-Peterson (RP) and Henry model for the dyes and toxins, respectively. For the multicomponent system were used Extended Langmuir (EL), Langmuir Interaction Factor (LIF), Extended Langmuir-Freundlich (ELF), Redlich- Peterson Interaction Factor (RPIF) models and the Ideal Adsorbed Solution Theory (IAST) model. The dye adsorption mechanism in the LDH and carbons were evaluated using Monte Carlo approach. The influence of pH, contact time and initial concentration were of extreme importance for the understanding of adsorption processes in the respective materials for each contaminant and each analyzed system. The implemented isotherm models were suitable for adsorption of contaminants represent the data in the single system. For the binary system involving dyes models were unsatisfactory. The quantities of absorbed contaminants were very representative for all materials evaluated in single and multicomponent systems, which suggests that promising in water and wastewater treatment processes. The results suggest that the molecular simulation can be used as a useful tool for material characterization and elucidation of the quantitative adsorption of contaminants.